HUBUNGAN KARAKTERISTIK INDIVIDU DAN KEPUASAN KERJA TERHADAP KINERJA KADER LANSIA PADA POSYANDU LANSIA - I Dewa Agung Gde Fanji Pradiptha; Made Budiawan; I Made Kusuma Wijaya; Galih Gayatri (Jurnal Keperawatan Malang, 2025)
Background: The increase in non-communicable diseases over the last 30 years in Indonesia requires early prevention and risk control. Puskesmas is the spearhead in improving the health status of the community through health cadres. Efforts to improve the role and function of Posyandu are not solely the responsibility of the government, but all components in the community, including the role of cadres. In addition to providing health information to the community, cadres also act as community mobilisers to come to Posyandu and implement clean and healthy living behaviours. Purpose: This study aims to analyse the relationship between individual characteristics and job satisfaction on the performance of elderly cadres at the elderly posyandu. Methods: This study is a correlational study with a cross sectional approach with a total sampling technique with a sample of 34 elderly cadres. Data collection instruments using questionnaires and observation sheets. Data analysis using chi square test. Result: The results showed that there was no significant relationship between age and the performance of elderly cadres with a p value = 0.566, there was no significant relationship between education and the performance of elderly cadres with a p value = 0.474, there was no significant relationship between tenure and the performance of elderly cadres with a p value = 0.292 and there was a significant relationship between job satisfaction and the performance of elderly cadres with a p value = 0.001. Implication: This research can be used as a reference for future researchers to conduct more in-depth research related to the relationship of individual characteristics to performance and factors that influence job satisfaction